Recurrent Periclitoreal Abscess Due To Birth Injury: A Case Report - Özdemir, Suna; Gezginç, Kazım; Mahmoud, Alaa (Gynecology Obstetrics & Reproductive Medicine, 2009)
Periclitoral abscess is a rare cause of severe vulvar pain and exceedingly infrequent occurance after perineal injury of vaginal birth. Case: A 39-year-old woman was presented with severe tenderness and swelling of her clitoris. She had been similar complaints for approximately 2 years with multiple rounds of antibiotics after her last vaginal birth including injury of periclitoral region. Treatment consisted of a wide local drainage of the abscess, and restoration of the periclitoral area. Healing was not delayed and no discomfort has been reported postoperatively. Curative theraphy of a recurrent clitoral abscess can be accomplished by surgical treatment with preservation of the clitoris.